COMPARISON OF ULTRASOUND-GUIDED LUMBAR ERECTOR SPINAE PLANE BLOCK AND TRANSMUSCULAR QUADRATUS LUMBORUM BLOCK FOR POST-OPERATIVE ANALGESIA IN TOTAL HIP REPLACEMENT SURGERIES: A PROSPECTIVE RANDOMIZED STUDY - SANGEETHA C; MALATHI ANIL KUMAR; VIJAYAKUMAR M HEGGERI; APARNA BATHALPALLI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of the study is to compare the efficacy of ultrasound-guided lumbar erector spinae plane block (ESPB) and transmuscular quadratus lumborum block (QLB) in providing post-operative analgesia for patients undergoing total hip replacement (THR) surgeries. Methods: This prospective, randomized, double-blind study compared the efficacy of ultrasound-guided lumbar ESPB and transmuscular QLB (QLB-t) for post-operative analgesia in THR surgeries. Ninety patients were randomized into three groups: ESPB, QLB, and a control group. Primary outcomes included the duration of analgesia, measured by numeric rating scale scores, and secondary outcomes assessed total analgesic consumption and the incidence of post-operative nausea and vomiting (PONV) within 24 h. For statistical purposes, p<0.05 was taken as statistically significant. Results: This study compared lumbar ESPB and QLB for post-operative analgesia in THR surgeries. At the 1st h, pain scores were significantly lower in the ESPB (1.30) and QLB (1.05) groups compared to the control group (2.15) (p<0.001). Tramadol consumption in the first 12 h was significantly lower in the ESPB (52.3 mg) and QLB (50.1 mg) groups compared to the control group (135.20 mg) (p<0.001). PONV was absent in 60% of ESPB and 63% of QLB patients, compared to only 33% in the control group (p=0.038). Conclusion: Lumbar-ESPB and QLB-t blocks effectively reduce post-operative pain and analgesic requirements in THR surgeries, showing comparable benefits. Both techniques also lower the incidence of PONV.